A numerical investigation on optimization of PV/T systems with the field synergy theory. (25th February 2021) - Shen, Chao; Zhang, Yingbo; Zhang, Chunxiao; Pu, Jihong; Wei, Shen; Dong, Yu
Highlights: The special cooling channel based on field synergy theory was proposed. The optimal structural parameters of the special channel were determined. The effect of solar radiation and mass flowrate on PV/T system was investigated. Abstract: High cell temperature of PV modules would reduce electrical efficiency and hinder the development of photovoltaic application. Many potential cooling channels have been proposed for PV modules cooling but perform inefficiently, due to the insufficient heat transfer between the cooling water and PV modules. In current research, a PV/T system with a special cooling channel based on field synergy theory, was designed to optimize the performance of PV/T systems. The performance of the new PV/T system was studied numerically, and mathematical models were validated with the experimental data. Results indicated that electrical efficiency of PV modules increased by 0.5% (from 11.4% to 11.9%) when the solar radiation decreased from 1200 to 300 W/m 2 . The electrical efficiency increased 1.11% (from 10.8% to 11.9%) as the inlet mass flowrate of cooling water increased from 0.0018 to 0.018 kg/s at the inlet temperature of cooling water of 20 °C. Additionally, the special channel with shark dorsal fin type sawtooth or regular type sawtooth, had the optimal parameter values, with the channel depth of 0.05 m, the sawtooth peak of 0.035 m and the sawtooth width of 0.01 m. The average cell temperature with the optimized channel was 6.05 °C lower than the conventional smooth channel, and the new cooling channel performed better with a high solar radiation.